Peranan Stakeholders ii Kabupaten Bungo, Jambi dalam Pencegahan Praktek Alih Fungsi Lahan Pertanian ke Non-Pertanian: Tinjauan dari Perspektif Governance - Dolly, Fajar Ifan; Purnaweni, Hartuti; Kismartini, Kismartini; Susanti AS, Mey (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2022)
This paper elaborates about how the role of stakeholders viewed from the perspective of good governance, namely government, community and private sector in Bungo Regency, in preventing the conversion of agricultural land to other uses. This study uses qualitative methods and descriptive analysis. The results showed that importance of stakeholders in terms of a good governance perspectiveincluding : 1) The role of the Bungo Regency government in the principles of good governance, namely (1) legal certainty, including having prepared regulations to limit community activities in the use of agricultural land to other uses by assigning a regional regulation on land determination of sustainable agriculture (Perda Bungo Regency No. 7/2014), then every community or agency proven to have intentionally carried out the activity of converting productive agricultural land to get dis-incentives in the form of administrative sanctions and penalties from the Bungo Regency government. Furthermore, from the principles of good governance, namely (2) Accountability:Bungo Regency government has tried to maintain and protect active agricultural land in rural areas by making special restrictions on active horticultural agricultural land. The Bungo Regency Agriculture Service also continues to convey the progress of activities to the government in an effort to maintain agricultural land in villages close to urban areas. Next is the principle of good governance as seen from indicators (3) Transparency: including continuing to carry out FGD (Focuss Group Discussion) activities with agricultural stakeholders consisting of GAPOKTAN, farmers, Agricultural Counsellor Officers, and community in order to remind each other and coordinate not to use agricultural land for other uses. However, prevention efforts carried out by implementers in the field have not consistently enforced existing rules. Furthermore, the commitment of officers is still low so that the practice of land conversion is still often carried out by the community in the context of development and for plantation land. The Bungo Regency Agriculture Office is also overwhelmed by the people who own the land, who are difficult to work with. The role of the community (farmer groups, farmers, researchers, and agricultural observers) is only to help the government carry out early socialization of the positive values ​​of farming to the community, provide input and conduct supervision on other forms of agricultural land use activities to sub-district field officers. Meanwhile, the role of the private sector includes carrying out social responsibility and lobbying for cooperation with the Bungo Regency government.